Analisis Pelaksanaan Eksekusi Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 8/PUU-XVII/2019 - Firda Rizqika (Jurnal Ilmu Hukum, 2022)
ABSTRACTThis study aims to determine the changes in the rules for Implementing the execution of fiduciary guarantees after the Constitutional Court's decision, analyze the problems that arise before the decision. And the reconstruction of the rules after the Constitutional Court's decision. This research is a normative research based on the rule of law and decisions. The results showed that the rules for execution of guarantees before the Constitutional Court's decision caused violations of the debtor's rights such as threats, violence. Meanwhile, after the decision of the Constitutional Court, the arrangement must go through a court decision which is considered to provide more guarantee and legal certainty for the parties. Changes in the rules for implementing executions need to be accompanied by socialization of the rules, and ease of decision making so as to create legal awareness in the community.ABSTRAKPenelitian ini bertujuan untuk mengetahui perubahan aturan pelaksanaan eksekusi jaminan fidusi pasca putusan MK, menganalisis permasalahan yang timbul sebelum adanya putusan. Dan rekonstruksi aturan pasca putusan MK.Penelitian ini merupakan penelitian normative yang didasarkan pada aturan hukum dan putusan. Hasil penelitian menunjukkan bahwa aturan eksekusi jaminan sebelum adanya putusan MK menimbulkan pelanggaran hak debitur seperti pengamncaman, kekerasan. Sedangkan setelah adanya putusan MK pengaturan harus melalui putusan pengadilan dirasa lebih memberikan jaminan dan kepastian hukum bagi para pihak. Perubahan aturan pelaksanaan eksekusi perlu dibarengi dengan sosialisasi aturan, dan kemudahan dalam putusan sehingga menimbulkan kesadaran hukum di masyarakat.